Effect of Vegetarian Diet and Functional Meat Based Diet on Serum Lipid Profiles, Liver Functions and Oxidative Stress Related Indices: A Mice Model Study - Biswas, A.K.; Kumar, S.; Gopi, M.; Sahoo, M. (Journal of Meat Science, 2018)
Epidemiological evidence suggests that intake of high amount of non-vegetarian diet is associated with increased risk of chronic diseases  including atherosclerosis, hyperlipidemia and cancers. But, the research study on the effect of functional meat product in physiological  functions of health is still pending. Therefore, the aim of this study was to elucidate effect of whole grain cereal flours and some plant  derived bioactive compounds intake on antioxidant activity, MDA content, serum lipid profile, hepatic and renal functions and tissue  histopathology of vital organs were examined in mice model study. For this, a total thirty six adult male Swiss albino mice were randomly  divided into three groups (3×12): one group fed control diet (vegetarian diet, CD), another group fed control wafers (CW) and the third  group fed functional wafers (FW). The FW contained whole grain oat and sorghum flours, apple peel paste, oregano, aloe vera gel and  vitamin E. Result indicated that FW lowered overall serum total cholesterol (TC) and LDL-C levels but HDL-C remain unchanged.  Compared with control group, the TC and LDL-C in FW group were lowered by 15.61 and 16.51 mg/dL, respectively. The TGL was  lowest in mice received CD. The serum glucose level was decreased in CW and FW fed mice. The activity of hepatic and renal enzymes  were lowered (P
Keywords: Functional meat products; Glycemic index; Oxidative stress; Antioxidants; Hepatic and kidney disorders; Lipid profiles